Circulating NK cells and their subsets in Behçet's disease. (13th March 2017) - Hasan, M. S.; Ryan, P. L.; Bergmeier, L. A.; Fortune, F.
Summary: Behçet's disease (BD) is an autoinflammatory, chronic relapsing/remitting disease of unknown aetiology with both innate and acquired immune cells implicated in disease pathogenesis. Peripheral blood natural killer (NK) cells and their CD56 Dim /CD56 Bright subsets were surface phenotyped using CD27 and CD16 surface markers in 60 BD patients compared to 60 healthy controls (HCs). Functional potential was assessed by production of interferon (IFN)‐γ, granzyme B, perforin and the expression of degranulation marker CD107a. The effects of disease activity (BD Active versus BD Quiet ) and BD medication on NK cells were also investigated. Peripheral blood NK cells ( P < 0·0001) and their constituent CD56 Dim ( P < 0·0001) and CD56 Bright ( P = 0·0015) subsets were depleted significantly in BD patients compared to HCs, and especially in those with active disease (BD Active ) ( P < 0·0001). BD patients taking azathioprine also had significantly depleted NK cells compared to HCs ( P < 0·0001). A stepwise multivariate linear regression model confirmed BD activity and azathioprine therapy as significant independent predictor variables of peripheral blood NK percentage ( P < 0·001). In general, CD56 Dim cells produced more perforin ( P < 0·0001) and granzyme B ( P < 0·01) expressed higher CD16 levels ( P < 0·0001) compared to CD56 Bright cells, confirming their increased cytotoxic potential with overall higher NK cell CD107a expression in BD compared to HCs ( P < 0·01). Interestingly, IFN‐γ production and CD27 expression were not significantly different between CD56 Dim /CD56 Bright subsets. In conclusion, both BD activity and azathioprine therapy have significant independent depletive effects on the peripheral blood NK cell compartment. Abstract : NK cells and their CD56Dim/CD56Bright subsets were investigated in BD patients and compared to healthy controls by flow cytometry using CD27/CD16 surface markers with functional potential assessed by Perforin and IFN‐g production. The effects of disease activity (BDActive vs. BDQuiet) and BD medication on NK cells were also investigated.